Tunable Sub-Nanosecond Ultra Wideband Narrow Pulse Generator For Microwave Imaging - Zalzala, Ali Mahdi Jaafar (2016)
In recent years, the Ultra Wideband (UWB) technology-based systems exhibited higher performance metrics over narrow band communication systems. The UWB microwave imaging is an emerging application in the biomedical, object detection, and ranging fields. The Narrowband Pulse Generator (NPG) is an essential element of any UWB imaging system and its characteristics partially determine the overall performance of the system. Numerous NPG designs have been developed for specific types of applications and most of them designed for CMOS technology integration. Additionally, they lack the flexibility of user pulse width tuning. In this research, the main contribution is the design of a low-cost sub-nanosecond NPG with many features like tunable pulse duration and to generate a pulse shape with ultrafast rise and fall times that could enhance the quality of UWB microwave images. The design aims to reduce the NPG cost with the use of off-the-shelf components. The very low pulse transition times led to higher BW values in the frequency spectrum and would presage to enhance the quality of images been reconstructed from UWB radar imaging systems. The shortest pulse provided by the proposed NPG is about 820 ps with a fall time of about 64 ps and a pulse level of 200 mV (single-ended). The aforementioned pulse data has been simulated in a locally developed image reconstruction algorithm (EDAS) to detect hypothetical objects and the resultant images show significant quality enhancement in comparison to a Gaussian pulse (or its derivative) with an equivalent duration. Image entropy values have been reduced from 248 to 51. This simulation validated the concept of trapezoidal pulse (or its derivative) influence on image resolution. For a further validation, an experimental UWB imaging system has been configured with a circular array of antennas to detect and locate different targets made of selected materials. The proposed NPG pulses have been applied, after amplification, to the above system. The reconstructed images compared to those obtained from other pulse sources like the VNA and PPG. The images generated from the proposed NPG show better quality in most cases. Compared to VNA images, image entropy values dropped from 63.66 to 43.23 for clay rod, and from 143.77 to 46.50 for an Aluminum rod. The promising results of the proposed NPG can hopefully be applied as a useful tool to obtain higher resolution images and better target detection accuracy in many industrial applications.